Ice-tethered observational platforms in the Arctic Ocean pack ice. Issue 23 (2016) - Berge, Jørgen; Geoffroy, Maxime; Johnsen, Geir; Cottier, Finlo; Bluhm, Bodil; Vogedes, Daniel
Abstract: The Arctic Ocean faces rapid climate change, which impacts both physical and biological components of the marine ecosystem. Due to complicated and costly logistics inherent to sampling ice-covered areas, most studies conducted in the Arctic are based on relatively short-term sampling (weeks to months) centered around the minimum ice season. Given the need for longer-term monitoring, several autonomous ice-tethered observational platforms have been developed and deployed in the Arctic since the last decade. This review outlines their abilities, conception, and limitations. Most platforms were developed to measure physical data, which highlights a critical need for ice-tethered observatories monitoring biological processes.